System of systems engineering for border security and immigration: methodologies, processes and tools. (2nd February 2010) - Keating, Charles; Rabadi, Ghaith; Landaeta, Rafael E.; Bowling, Shannon
The purpose of this paper is to examine the nature and utility of methodology, methods and tools to support performance of system of systems engineering (SoSE). To achieve this purpose, three primary objectives will be pursued: 1) establish the critical issues in SoSE that impact the selection, deployment and development of supportive methodologies, methods and tools; 2) identify and assess current methodologies, methods and tools used in support of SoSE; 3) develop implications for practitioners and researchers concerning implications for performance of practice and research for SoSE in border security and immigration. The paper begins with an essential overview of the field of SoSE, highlighting the particular nature of methodologies, processes and tools to support effectiveness in SoSE. Second, the current state of SoSE supporting methodologies, processes and tools is developed. Of specific interest in this examination is the delineation of the findings with respect to 'traditional' systems engineering. Third, the spectrum of methodologies, methods and tools is placed within the context of SoSE, with examination of the implications for practice and research. The paper concludes with an organisation of a current set of SoSE supporting methodologies, processes and tools that can assist practitioners performing particular functions in an SoSE-based application.